The Role of Cultural Sufism Education in Efforts to Strengthen Religious Moderation in Multicultural Societies - Giyarsih (PT. Islamic Research Publisher, 2023)
.This research aims to discuss the educational role of cultural Sufism teachings in strengthening religious moderation in society. This research adopts a qualitative approach by applying descriptive-analytical methods. The type of data collected in this research is qualitative and not in the form of statistical figures. The main research data sources include literature related to cultural Sufism, religious moderation, and wahidiyah teachings. In addition, secondary sources for this research include references related to the main topic, taken from articles, books, and documents from previous research. The results of this research show that the role of wahidiyah as one of the products of cultural Sufism in Indonesia in strengthening religious moderation can be seen from the implementation of wahidiyah teachings, especially wahidiyah teachings which cover the social field, namely: 1) the principle of indiscriminate broadcasting and development of wahidiyah ; 2) Group division is based on general social differentiation in society, they have the same rights and obligations; 3)